GADGET, MORAL DAN SYARIAT: PERSPEKTIF PENDIDIKAN HUKUM PIDANA ISLAM UNTUK GENERASI DIGITAL DI MTSS DARUL ULUM SASA KOTA TERNATE - Sitti Nurchalifa Umaternate; Zainuddin Arifin; Nursinita Killian; Musaddi Din; Siti Melandari Abdullah (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
The development of digital technology has brought significant changes to patterns of social interaction and character formation among young generations, including within the madrasah environment. Uncontrolled use of gadgets has the potential to lead to moral degradation, behavioral deviance, and violations of legal and Islamic norms. This community service program aims to provide preventive education based on Islamic criminal law to students of MTsS Darul Ulum Sasa, Ternate City, in order to foster wise and responsible use of gadgets.The implementation methods included interactive counseling sessions and participatory discussions. The materials covered the basic concept of jarimah in Islamic criminal law, the principle of protecting honor (hifz al-‘ird), the protection of intellect (hifz al-‘aql), and their relevance to social media ethics and potential digital offenses such as the dissemination of negative content. The results of the program indicate a significant improvement in students’ understanding of the moral and legal consequences of gadget misuse. Furthermore, there was increased awareness of the importance of upholding Islamic values as guidance in daily digital activities. This program recommends strengthening digital literacy based on Islamic values through collaboration among schools, parents, and higher education institutions to prevent potential legal violations in the digital era